Seven in Absentia E3 Ubiquitin Ligases: Central Regulators of Neural Cell Fate and Neuronal Polarity - Ong, Taren; Solecki, David J. (Frontiers in Cellular Neuroscience, 2017)
During neural development, neural precursors transition from a proliferative state within their germinal niches to a migratory state as they relocate to their final laminar positions. Transitions across these states are coupled with dynamic alterations in cellular polarity. This key feature can be seen throughout the developing vertebrate brain, in which neural stem cells give rise to multipolar or unpolarized transit-amplifying progenitors. These transit-amplifying progenitors then expand to give rise to mature neuronal lineages that become polarized as they initiate radial migration to their final laminar positions. The conventional understanding of the cellular polarity regulatory program has revolved around signaling cascades and transcriptional networks. In this review, we discuss recent discoveries concerning the role of the Siah2 ubiquitin ligase in initiating neuronal polarity during cerebellar development. Given the unique features of Siah ubiquitin ligases, we highlight some of the key substrates that play important roles in cellular polarity and propose a function for the Siah ubiquitin proteasome pathway in mediating a post-translational regulatory network to control the onset of polarization.